2010
DOI: 10.2353/ajpath.2010.090355
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Function of Cellular Prion Protein in a Mouse Model of Amyotrophic Lateral Sclerosis

Abstract: Transgenic mice expressing human mutated superoxide dismutase 1 (SOD1) linked to familial forms of amyotrophic lateral sclerosis are frequently used as a disease model. We used the SOD1 G93A mouse in a crossbreeding strategy to study the function of physiological prion protein (Prp). SOD1 G93APrp؊/؊ mice exhibited a significantly reduced life span, and an earlier onset and accelerated progression of disease, as compared with SOD1 G93APrp؉/؉ mice. Additionally, during disease progression, SOD1 G93APrp؊/؊ mice s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 64 publications
0
21
0
Order By: Relevance
“…Accordingly, it was recently shown that hop/STI1 enhanced self-renewal of stem/progenitor cells through its interaction with PrP C , and, again, the hop/STI1 230-245 peptide by itself had no effect [179]. A likely explanation for these data is that signaling leading to proliferation of either the glioma or the stem/progenitor [230][231][232][233][234][235][236][237][238][239][240][241][242][243][244][245] to PrP C . The flexible N-terminal tail was omitted for clarity; d, e lowresolution models (sets of grey spheres) of either hop/STI1 alone (d), or the hop/STI1:PrP C complex (e), generated from SAXS measurements, reveal a compaction of the tertiary structure of hop/STI1 upon binding to PrP C (arrow points to PrP C , where the globular domain is shown in yellow and the flexible N-terminal tail is shown in pink).…”
Section: Reciprocal Remodeling Upon Binding Of Prp C and Hop/sti-1mentioning
confidence: 82%
“…Accordingly, it was recently shown that hop/STI1 enhanced self-renewal of stem/progenitor cells through its interaction with PrP C , and, again, the hop/STI1 230-245 peptide by itself had no effect [179]. A likely explanation for these data is that signaling leading to proliferation of either the glioma or the stem/progenitor [230][231][232][233][234][235][236][237][238][239][240][241][242][243][244][245] to PrP C . The flexible N-terminal tail was omitted for clarity; d, e lowresolution models (sets of grey spheres) of either hop/STI1 alone (d), or the hop/STI1:PrP C complex (e), generated from SAXS measurements, reveal a compaction of the tertiary structure of hop/STI1 upon binding to PrP C (arrow points to PrP C , where the globular domain is shown in yellow and the flexible N-terminal tail is shown in pink).…”
Section: Reciprocal Remodeling Upon Binding Of Prp C and Hop/sti-1mentioning
confidence: 82%
“…Mice at terminal disease stage were anesthetized and transcardially perfused with PBS for cryoconservation of the tissue or by PBS followed by paraformaldehyde in case of subsequent paraffin embedding as published elsewhere [16]. Prepared were the spinal cords as well as the whole brains separated sagittally into the two hemispheres.…”
Section: Tissue Preparationmentioning
confidence: 99%
“…Recently, some of us investigated the neuroprotective function of cellular prion protein in a mouse model of SOD1 linked amyotrophic lateral sclerosis which was characterized by rapid degeneration of motor neurons in spinal cord. 3 Due to the small sample size (2-5 mm 2 ) investigation of the metal distribution in mouse spinal cord requires powerful quantitative imaging techniques with higher spatial resolution than required for brain. Laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) as elemental mass spectrometry has been established for bioimaging of trace metals, especially for the essential transition metals Fe, Cu, Zn, and of selected non-metals (such as C, P and S) in our BrainMet (Bioimaging of Metals in Brain and Metallomics) laboratory at Forschungszentrum Ju¨lich.…”
Section: Introductionmentioning
confidence: 99%
“…A series of recent and ongoing studies has assessed pain, inflammatory or degenerative pathophysiology. [1][2][3] Popular animal models which have been assessed in this scope were unilateral limb lesions, experimental autoimmune encephalomyelitis (EAE) or animals transgenic for proteins involved in redox and free radical metabolism. In several cases where the systemic central nervous system is affected the pathology of the spinal cord is most informative and the brain only a side scene.…”
Section: Introductionmentioning
confidence: 99%